Review on the Recent Advances in the Impulsive Control Strategy Based Coordination of the Multi-agent Systems - TAN Xuegang; CAO Jinde (Nantong Daxue xuebao. Ziran kexue ban)
The impulsive control strategy has attracted the immense research attention due to its excellent performance in terms of the robustness, the simplicity and the convergence, which has widely been utilized to solve the coordinated control problems of multi-agent systems. This paper presents a systematic review on the recent advances in the impulsive control strategy of multi-agent systems, and mainly introduces the design of the impulsive control protocols and the schemes of impulse sequence generation. In addition, the practical applications for the impulsive-control based coordination of multi-agent systems are still introduced. Finally, some open and pressing issues on the distributed impulsive control based coordination of multi-agent systems, their theoretical and application research prospect are provided.